Echocardiography in Healthy Dogs - Comparison of Apical 5C and Subxiphoid Windows - Marques, Daniele Clímaco; Rodrigues, Renan Paraguassu de Sá; Carvalho, Paulo Vitor Silva de; da Silva, Andrezza Braga Soares; Leitão, Kelvin Ramon da Silva; Sousa, Francisco das Chagas Araújo; Barbosa, Maria Angelica Parentes da Silva; Alves, Jacyara de Jesus Rosa Pereira; Costa, Amilton Paulo Raposo; Alves, FLávio Ribeiro (Acta Scientiae Veterinariae, 2024)
Background: Echocardiography is one of the most used diagnostic methods in Veterinary Cardiology for the investigation of heart diseases. This stands out for being a non-invasive technique, readily available and that generates satisfactory results in hemodynamic monitoring compared to other invasive techniques. However, some parameters are still not well established in Veterinary Medicine. This work aims to perform a comparative echocardiographic study of the hemodynamic profile of the outflow tract of the left ventricle (LVOT) between the apical 5-chamber and subxiphoid windows in healthy dogs, in order to characterize the difference between their hemodynamic indices. Materials, Methods & Results: An observational, prospective study was carried out in which 30 clinically healthy dogs of both sexes of small to medium-sized breeds were examined. All animals underwent a complete screening echocardiographics examinations without sedation. After the complete examination, the left ventricular outflow tract (LVLVD) internal diameter was measured in the parasternal window on the long axis at the level of the aortic valve annulus during systole. The LVOT cross-sectional area was calculated using the formula πr2. The LVOT velocity-time integral (VTI) was measured by pulsed Doppler, with the cursor positioned before the aortic valve in the apical 5-chamber and subxiphoid window. Stroke volume (SV) was the result of the product of LVOT IVT measurements and LVOT crosssectional area. Cardiac output (CO) was estimated by the product of SV and heart rate (HR). VTI, SV and DC were comparable between the 2 groups and showed a statistically significant difference (P < 0.05). The values for the subxiphoid window were higher compared to the values found in the apical 5-chamber window. Discussion: CO and SV can be underestimated when VTI is measured with the probe in an apical position. With the results of the present research, it is speculated that the measurement of the LVOT flow in a subxiphoid position is the method of choice for the acquisition of more accurate data on CO and SV. This difference in precision is justified by the dependence of the Doppler beam on alignment with blood flow. A Doppler signal with an intercept angle closer to 0° is preferable to obtain reliable values. The subxiphoid transducer provides more consistent alignment of the ultrasound beam with the aortic blood flow. Previous studies in humans have reported that vessel diameter has a greater relevance in the variation of cardiac output. In the present study, the variables that presented the highest correlation value were the LVSD and CO, in both acquisition methods. Studies performed in humans have suggested that cardiac output and VTI do not correlate with body index or weight, concluding that vessel diameter has a greater relevance in the variation of cardiac output. In line with previous human studies, the LVOT VTI allows for early identification of cardiogenic shock. In dogs, it has been used as a substitute for SV. This approach eliminates errors in the determination of the LVOT cross-sectional area defined by the formula πr2. In addition, the VTI has also been used in therapeutic guidance regarding fluid responsiveness. In these circumstances, the level of sensitivity and precision of the LVOT flow measurement becomes worrying, since the present research demonstrates a variability of hemodynamic profiles between 2 acquisition techniques in healthy dogs. Future studies are needed to investigate its application in Veterinary Medicine, in addition, studies involving reference data are needed. Keywords: canines, Doppler, diagnostic imaging, cardiology, cardiovascular diseases, hemodynamics, LVLVD, LVOT.